A new species of the laomediid mud shrimp genus Naushonia Kingsley, 1897 (Decapoda: Gebiidea) from Japan - Komai, Tomoyuki; Hirabayashi, Isao (Zootaxa, 2020)
A new species of the laomediid mud shrimp genus Naushonia Kingsley, 1897, N. kiiensis, is described and illustrated on the basis of a single male specimen from Kii Peninsula, central Japan, at a sublittoral depth of 14 m. The new species is morphologically closest to N. serratipalma Komai & Anker, 2010, known from French Polynesia and the Red Sea coast of Saudi Arabia, among the 15 known congeners, but is distinguished from the latter by the spinulose middorsal and submedian gastric carinae on the carapace, the rugose posterior dorsum of the carapace, stronger but fewer spines on the distomesial lobe of the pereopod 1 merus and fewer spinules consisting of the serration of the palm lateral margin. From Japanese waters three species have been recorded, of which only N. japonica Komai, 2004 is known from the temperate mainland. The new species is the second occurring in the Japanese mainland.